2020
DOI: 10.1111/coa.13668
|View full text |Cite
|
Sign up to set email alerts
|

Survival and treatment outcome of head and neck cancer patients with pulmonary oligometastases

Abstract: Objectives The purpose of this study was to determine the outcome of head and neck squamous cell carcinoma (HNSCC) patients developing lung metastasis. Design Retrospective study. Participants HNSCC patients with lung metastasis treated between 2001 and 2018 were included. Mean outcomes measures Statistical analyses described the relationship between patient survival, treatment efficacy and pulmonary metastasis occurrence. Results One hundred HNSCC patients were included in the study. The median overall surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
1
6
1
Order By: Relevance
“…Meanwhile, the histological subtypes of head and neck cancer are known to be factors affecting prognosis. SCC is the most common head and neck cancer and has more aggressive features and a worse prognosis than other subtypes [4,10]. In the present study, the 5-year DFSRs of patients with SCC and ACC after pulmonary metastasectomy were 39.9% and 32.4%, respectively, and there was no statistically significant difference between them.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…Meanwhile, the histological subtypes of head and neck cancer are known to be factors affecting prognosis. SCC is the most common head and neck cancer and has more aggressive features and a worse prognosis than other subtypes [4,10]. In the present study, the 5-year DFSRs of patients with SCC and ACC after pulmonary metastasectomy were 39.9% and 32.4%, respectively, and there was no statistically significant difference between them.…”
Section: Discussioncontrasting
confidence: 45%
“…In general, it has been reported that pulmonary metastasis of head and neck cancer is incurable and has a very poor prognosis [1, 2]; traditionally, treating the disease systemically instead of surgically has been preferred [3]. However, recent studies reported that the treatment outcome of patients with distant metastasis of head and neck cancer varies depending on the ranges of metastasis (isolated or disseminated disease), histology [4, 5], treatment modalities [1], biological profiles, and disease-free interval (DFI) [6, 7]. Nevertheless, patients with distant metastasis of head and neck cancer have only been classified as M1, and there is no specific guideline based on factors that influence treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Ricco et al reported SBRT treatment in patients with pulmonary oligometastases of different primary tumors, using a dose of 48-54 Gy divided into 3-5 fractions, and the 1-year OS and LC rates were 74.1% and 80.4%, respectively (20). Lardinois et al retrospectively analyzed 100 patients with head and neck squamous cell carcinoma with lung metastases, and the median OS and recurrence-free survival rates were 21 and 7 months, respectively (21). This study found that the median OS, LC, and PFS rates were 24.9, 25.9, and 11.8 months, respectively, and these were similar to the results of related studies.…”
Section: Discussionmentioning
confidence: 99%
“…In most studies, the risk factors related to OS, LC, and PFS include functional status, lesion diameter, primary tumor type, number of metastases, history of local metastases, and the number of metastatic organs throughout the body. Lardinois et al found that the survival time of patients with single lung metastasis was signi cantly prolonged, and the local control rate of the site of metastasis was better than those of patients with multiple lung metastases (P < 0.001) (21). Yamamoto et al reported that functional status PS was an independent prognostic factor for OS (PS 1 vs. PS 0, p = 0.0 2; PS 2-3 vs. PS 0, p = 0.0 4) ( 22).…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy 3 [7] 12 [15] 3 [7] 5 [12] Combination therapy 8 [19] 18 [23] 8 [19] 11 [26] Else 7 [16] 15 [19] 7 [16] 6 [14] Adjuvant than that of the chemotherapy group before matching (Figure 2) (P<0.05), and the result was still the same after matching (Figure 3) (P<0.05). After matching, the 3-year OS rates of the surgery and chemotherapy groups were 85.1% and 67.1%, respectively, the 5-year OS rates were 75.1% and 48.0%, and the median OS were 79 months (95% CI: 61.99-96.02 months) and 53 months (95% CI: 28.31-77.69 months), respectively.…”
Section: Survival Data For Patientsmentioning
confidence: 98%